Efficient distributed address assignment algorithm based on topology maintenance in ZigBee networks - YAO, Yu-kun; WANG, Guan; REN, Zhi; LI, Peng-xiang; CHEN, Yong-chao (Journal of China universities of posts and telecommunications, 2013)
Adopting the borrowed address algorithm can decrease the orphan nodes in ZigBee networks that use distributed address assignment mechanism （DAAM）. The existing borrowed address algorithms can increase the success rate of address assignment, but they have defects such as greater cost of overhead and time in founding network caused by breaking topology. To solve such problems, we propose an more efficient distributed borrowed address assignment algorithm based on topology maintenance （A2BTM） that has a topology maintenance function. It borrows address firstly from the offspring nodes in the same branch for the orphan nodes and replies distributed the request of the borrowed address message immediately, to maintain the network topology and decrease the overhead and time spent on the mechanism of borrowed address. Theoretical and simulation analyses manifest that AZBTM algorithm outperforms DAAM and its improved algorithms in terms of the overhead and time spent in founding network, on the premise of keeping a higher success rate of address assignment. Furthermore, A2BTM can lessen the influence from detour phenomenon efficiently.